Estimation of axially-loaded bored piles interaction in the design of pile foundation/Centriškai apkrautų gręžtinių polių tarpusavio sąveikos įvertinimas projektuojant polinius pamatus - Sližytė, Danutė (Journal of Civil Engineering and Management, 2001)
In Lithuania and many foreign countries traditional approach of replacing the pile group by equivalent raft foundation in order to estimate settlements is used. But now we have another method. H. Poulos [3] described the influence between piles in a pile foundation with the coefficient of interaction, that indicate the pile influence on the neighbouring piles settlement increasing neighbouring pile acted by axial load. General characteristics of Toyoura sand was shown in the table. With this data and two methods of calculation settlement of 5×5 pile foundation was founded (Fig 1) and results are shown in Fig 3. Also Fig 5 shows the effects of non-linearity on the axial load distribution between a piles of 5×5 group embedded in non-cohesive soil. The load distribution is expressed in terms of the ratio of load on pile to the average pile load in the group (N/Nav), and is plotted against the average pile load. The same figure shows how differ results when the normalised pile spacing 3D, 4,5D and 6D. In the case when the normalised pile spacing r/D = 3 and pile foundation work in elastic phase the corner piles take 19,5% larger load as the average pile load and central pile take 20,0% smaller load as the average pile load. But after increasing of the average load this difference decreases. This difference also decreases when the normalised pile spacing increases. Article in Lithuanian. First Published Online: 30 Jul 2012